Monitoring Microcirculatory Blood Flow with a New Sublingual Tonometer in a Porcine Model of Hemorrhagic Shock - Palágyi Péter; Kaszaki József; Rostás Andrea; Érces Dániel; Németh Márton Ferenc; Boros Mihály; Molnár Zsolt (Hindawi Publishing Corporation, 2015)
Tissue capnometry may be suitable for the indirect evaluation of regional hypoperfusion. We tested the performance of a new sublingual capillary tonometer in experimental hemorrhage. Thirty-six anesthetized, ventilated mini pigs were divided into sham-operated (n = 9) and shock groups (n = 27). Hemorrhagic shock was induced by reducing mean arterial pressure (MAP) to 40 mmHg for 60 min, after which fluid resuscitation started aiming to increase MAP to 75% of the baseline value (60-180 min). Sublingual carbon-dioxide partial pressure was measured by tonometry, using a specially coiled silicone rubber tube. Mucosal red blood cell velocity (RBCV) and capillary perfusion rate (CPR) were assessed by orthogonal polarization spectral (OPS) imaging. In the 60 min shock phase a significant drop in cardiac index was accompanied by reduction in sublingual RBCV and CPR and significant increase in the sublingual mucosal-to-arterial PCO2 gap (PSLCO2 gap), which significantly improved during the 120 min resuscitation phase. There was significant correlation between PSLCO2 gap and sublingual RBCV (r = -0.65, p < 0.0001), CPR (r = -0.64, p < 0.0001), central venous oxygen saturation (r = -0.50, p < 0.0001), and central venous-to-arterial PCO2 difference (r = 0.62, p < 0.0001). This new sublingual tonometer may be an appropriate tool for the indirect evaluation of circulatory changes in shock.